Four new Amynthas and Metaphire earthworm species from nine provinces in southern China - Sun, Jing; Jiang, Ji-Bao; Bartlam, Scott; Qiu, Jiang-Ping; Hu, Feng (Zootaxa, 2018)
Four new species belonging to genera Amyntha and Metaphire were discovered from an extensive area in southern China, covering the provinces Sichuan, Yunnan, Guizhou, Guangdong, Guangxi, Fujian, Hunan, Jiangxi and Anhui. The species are named Amynthas dispersus Sun & Qiu, sp. nov., Amynthas shanghangensis Sun & Qiu, sp. nov., Amynthas dentiformis Sun & Jiang, sp. nov. and Metaphire sanmingensis Sun & Jiang, sp. nov. The first two new species have four pairs of intersegmental spermathecal pores in 5/6–8/9. A. dispersus has elliptical and glandular male pore porophores raised on a low pad-like area surrounded by two to three shallow skin folds, the genital papillae are variable in the spermathecal pore and male pore regions, and prostate glands are vestigial or rudimentary. Amynthas shanghangensis has male porophores surrounded by three papillae, each prostate gland accompanied by an accessory gland, and the distal ½–⅓ of the spermathecal diverticulum dilated into a rod-shaped seminal chamber. Amynthas dentiformis has two pairs of spermathecal pores in 7/8–8/9, male pores always surrounded by two papillae, and small sacs on the dorsal and ventral margins of the intestinal caecae; the prostate gland occasionally has stalked accessory glands. M. sanmingensis is in the Metaphire houlleti-group, and has secondary male pores opening to copulatory pouches, rod-shaped spermathecal seminal chamber, as well as variable genital papillae in spermathecal and male pores regions. The GenBank accession numbers of DNA barcode data are attached under the description of each species.